Empowering Women Through the Making Soursop Jam in Bumi Jaya Village, Sukau Subdistrict, West Lampung Regency - Enggal Parikesit Santoso; Gusti Putu Dano Putra; Helvi Yanfika; Herman Yulianto; Irwan Effendi; Dewangga Nikmatullah (Research and Social Study Institute, 2023)
Soursop fruit is one of the commodities in Bumi Jaya village, where soursop fruit is a fresh fruit that is easily damaged and spoils quickly. Therefore, training is needed to deal with this problem. The purpose of this service activity is to increase public knowledge through training in making soursop jam. The activity was carried out in January 2023 in Bumi Jaya Village, Suka District, West Lampung Regency. Respondents in the activity were Team PKK. The method of implementation is survey, education/ speech, practice/demo and evaluation. From this community service activity, it shows that the people of Bumi Jaya Village are enthusiastic in participating in activities starting from the socialization stage to practice/demo on how to make soursop jam, thus increasing knowledge in processing soursop fruit into soursop jam which is useful in product diversification and increasing product shelf life.